The mediation effect of learning organization in the relationship between internal service quality and job satisfaction of nurses - Chrystelle Mayap Njilo; Georgiana Karadaş; Zanete Garanti (The Ethiopian Journal of Health Development, 2020)
Abstract Background: There is little evidence about the influence of internal service quality on nurses’ job satisfaction and their ability to provide efficient patient care. This study aims to explore the mediating effect of ‘learning organization in the relationship between the internal service quality and job satisfaction of nurses in public hospitals in Cameroon. Methods: A total of 400 questionnaires were distributed to nurses in public hospitals between 20 February to 31 December 2017. The mediation analysis was conducted using SPSS and PROCESS model 4. Results: The impact of internal service quality and learning organization on the job satisfaction of nurses was significant and positive. In addition, learning organization fully mediates the relationship between internal service quality and job satisfaction. Conclusions: Internal service quality increases the job satisfaction of health workers via learning organization practice in public hospitals. Health care managers should be aware of factors that foster job satisfaction and provide a high quality of internal services that incorporate learning organization activities, to enhance existing medical skills and improve the job satisfaction of health workers for better health service delivery to patients. [Ethiop. J. Health Dev. 2020; 34(4):286-292] Key words: Nurses, internal service quality, learning organization, job satisfaction